2021
DOI: 10.3390/cancers13164153
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of Prognostic and Immune Infiltrates for CXCs

Abstract: Background: CXCs are important genes that regulate inflammation and tumor metastasis. However, the expression level, prognosis value, and immune infiltration of CXCs in cancers are not clear. Methods: Multiple online datasets were used to analyze the expression, prognosis, and immune regulation of CXCs in this study. Network analysis of the Amadis database and GEO dataset was used to analyze the regulation of intestinal flora on the expression of CXCs. A mouse model was used to verify the fact that intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…For instance, CD93 was recently found to improve tumor vascular functions to promote T-cell infiltration and antitumor immunity after blockade of its pathway ( Sun et al, 2021 ). In addition, we also found that CD93 expression was positively related to almost all immune-related genes, which are known to promote the growth of tumor cells and tumor angiogenesis as well as contribute to tumor metastasis ( Li et al, 2021 ; Schaafsma et al, 2021 ) in nearly all cancers, which further demonstrated the importance of CD93 in the process of immune regulation.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, CD93 was recently found to improve tumor vascular functions to promote T-cell infiltration and antitumor immunity after blockade of its pathway ( Sun et al, 2021 ). In addition, we also found that CD93 expression was positively related to almost all immune-related genes, which are known to promote the growth of tumor cells and tumor angiogenesis as well as contribute to tumor metastasis ( Li et al, 2021 ; Schaafsma et al, 2021 ) in nearly all cancers, which further demonstrated the importance of CD93 in the process of immune regulation.…”
Section: Discussionsupporting
confidence: 53%
“…Single-cell transcriptome sequencing is a key technique for analyzing the underlying functions of candidate molecules at single-cell levels ( He et al, 2021 ; Li et al, 2021 ). In retinoblastoma (RB), the expression of LIPT1 was negatively associated with cell cycle, DNA repair response, EMT and invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our study also revealed the co-expression of FDX1 with immune-related genes, including chemokine, chemokine receptor, MHC, immunostimulatory, immunosuppressive, and immune checkpoint-related genes. FDX1 expression is closely correlated with almost all immune-related genes and contributes to tumor development ( Li et al, 2021 ; Schaafsma et al, 2021 ). Overall, these results indicate that the regulation of FDX1 expression may be a promising strategy to increase the efficacy of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%